Example-based learning in heuristic domains: can using relevant content knowledge support the effective allocation of intrinsic, extraneous, and germane cognitive load? - Udvardi-Lakos, Nina; Weirich, Marlene; Asbrand, Julia; Renkl, Alexander (Frontiers in Psychology, 2024)
Introduction Worked examples support initial skill acquisition. They often show skill application on content knowledge from another, “exemplifying” domain (e.g., argumentation skills have to be applied to some contents). Although learners’ focus should remain on the skill, learners need to understand the content knowledge to benefit from worked examples. Previous studies relied on exemplifying domains that are familiar and contain simple topics, to keep learners’ focus on skill acquisition. Aim We examined whether using a relevant exemplifying domain would allow learners to acquire both skills and content knowledge simultaneously, or whether relevant content distracts from the main learning goal of skill acquisition. Methods and results In a training study with 142 psychology students, we used example-based learning materials with an exemplifying domain that was either relevant or irrelevant for participants’ course outcomes. We assessed cognitive load, declarative knowledge about skills and course-related content knowledge, and argumentation quality. Incorporating relevant content knowledge in worked examples did not reduce learning outcomes compared to a condition using an irrelevant exemplifying domain. Discussion Contrary to previous research, the results suggest that worked examples with a relevant exemplifying domain could possibly be an efficient teaching method for fostering skills and content knowledge simultaneously.